Thermodynamic Tuning of Mg-Based Hydrogen Storage Alloys: A Review - Zhu, Min (Materials (Basel), 2013)
Mg-based hydrides are one of the most promising hydrogen storage materials because of their relatively high storage capacity, abundance, and low cost. However, slow kinetics and stable thermodynamics hinder their practical application. In contrast to the substantial progress in the enhancement of the hydrogenation/dehydrogenation kinetics, thermodynamic tuning is still a great challenge for Mg-based alloys. At present, the main strategies to alter the thermodynamics of Mg/MgH(2) are alloying, nanostructuring, and changing the reaction pathway. Using these approaches, thermodynamic tuning has been achieved to some extent, but it is still far from that required for practical application. In this article, we summarize the advantages and disadvantages of these strategies. Based on the current progress, finding reversible systems with high hydrogen capacity and effectively tailored reaction enthalpy offers a promising route for tuning the thermodynamics of Mg-based hydrogen storage alloys.